(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A recent study reveals that Isatinylthiosemicarbazone analogues inhibit mycobacterial growth by inhibiting the Isocitrate Lyase (ICL). Hence Two-dimensional (2D), Three-dimensional (3D), and Group QSAR (GQSAR) studies were performed to reduce the amount of pharmacophore needed to make effective ICL inhibitors. New Chemical Entities (NCEs) were created based on the findings of all QSAR studies. It was discovered that QSAR models produced noticeably positive statistical findings. i.e. (r2 > 0.7), cross-validation (q2 > 0.6), and external validation (pred_r2 > 0.6), indicating high predictability of all models. Utilizing molecular docking studies, the binding affinities of designed NCEs were investigated for the ICL enzyme (PDB code: 1F8M). The absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of designed NCEs were expected to have a pharmacokinetic profile similar to their drug. Overall, it is important to state that the methodology used for pharmacophore optimization using 2D, 3D, G-QSAR, and Molecular Docking ADMET research works was discovered to be extremely accurate.